(Re) conhecimento e uso de formigas na gestão de áreas protegidas: interações ecológicas e socioambientais na conservação - Rabelo, Mariana Azevedo (2021)
Although ants stand out for their high diversity, distribution and ecological relevance for ecosystems processes, the accumulated scientific knowledge about these organisms does not effectively apply in conservation actions, such as the planning and management of protected areas. This thesis presents the recognition and use of ants in the management of protected areas through ecological processes, social representation and knowledge exchange. To this end, it was evaluated: (i) whether different classification criteria for the degree of conservation of State Park areas in the Atlantic Forest can be considered good predictors for evaluating ecological processes performed by ants, and consequently the functioning of these ecosystems; (ii) how ants are represented by State interlocutors (managers and the management team), Society (visitors) and Academy (researchers), actors directly and indirectly involved in the conservation of protected areas, for building educational actions in State Parks. In a third approach, the experience report on the idealization, development and execution of the “Formigas em Ação” project was shared, an initiative that aims to carry out scientific dissemination about ants through the exchange of knowledge with different social groups, and thus promote reflections on the ecological and sociocultural importance of this group. It was shown that: (i) criteria for classifying the degree of conservation of areas based on subjective and technical knowledge are not good predictors for evaluating the ecological processes carried out by ants, but ecological criteria such as the richness of insect predatory ants influenced quantitatively the processes and must be considered in the assessments; (ii) State, Society and Academy present differences in representations about ants according to the social roles that each group plays in the context of management. The “Formigas em Ação” project proved to be a tool for scientific dissemination about ants by enabling ecological and sociocultural recognition by various social actors, in front of positive repercussion and the interest of children, young people and educators. It is estimated that the research presents an overview of the potential, weaknesses, gaps and challenges in the use and integration of scientific knowledge about ants and the knowledge of different social groups in promoting the conservation of protected areas. This research contributed to the recognition of the ecological importance of ants for the functioning of ecosystems and as a proposal for the beginning of the ecological, environmental, social and educational inclusion of these organisms in actions and management programs of State Parks that value, respect and integrate the individual and collective knowledge.